Environment and government policies in northern Nigeria - Freeman, H.A. (International Livestock Research Institute, 2004)
There is a widespread and growing concern about the extent and consequences of degradation of the natural resources base in many developing countries. This study explores the effect of selected economic policies on farm-household consumption and production choices in northern Nigeria and evaluates the consequences for environmental degradation at the farm level. Attention is focused on the household's ability to make productivity enhancing and land improvement investments. Insights are provided into the relative significance of nitrogen extracting vs. nitrogen contributing crops, on the incidence of likely biological constraints in the production system, and the influence of input use on land degradation. In this study, the economic response of archetype farm households to existing policies is determined from farm-household data,.This id done with a view to drawing inferences on the environmental consequences of these policies, to determine the impact of specific policy alternatives on the household's choice set and the implications they hold for the resource base. Topics of discussion include the effects of policies on household behaviour in the high performance zone; effects of policies on the environment; impact of ten percent increase in price of legumes; impact of neutral technical change in legumes; impact of eliminating fertiliser subsidy; and impact of eliminating fertiliser subsidy plus technical change in crop production. It also presents a descriptive overview of the analytical model; and looks into data sources, and the structure of a computable household model.